Signal-mediated import of bacteriophage T7 RNA polymerase into the Saccharomyces cerevisiae nucleus and specific transcription of target genes. - Benton, B M (1990)
Bacteriophage T7 RNA polymerase and derivatives that contain the nuclear localization signal (NLS) from simian virus 40 T antigen (J. J. Dunn, B. Krippl, K. Bernstein, H. Westphal, and F. W. Studier, Gene 68:259-266, 1988) were expressed in Saccharomyces cerevisiae under the control of the inducible GAL1 promoter. As determined by indirect immunofluorescence, T7 RNA polymerase lacking the NLS remained mostly in the cytoplasm, whereas the protein containing the NLS localized to the nucleus. T7 RNA polymerase containing a mutated NLS remained mostly cytoplasmic. Hybrid proteins containing the NLS near the amino terminus were enzymatically active in the yeast cell, initiating transcription selectively at a T7 promoter placed in yeast chromosomal or plasmid DNA and stopping at a specific T7 terminator. At limiting enzyme concentrations, 5 to 10 times as much target RNA was produced when the polymerase contained the NLS, presumably because more enzyme reached the nucleus. Although substantial amounts of intact mRNA accumulated, no translation of target mRNAs in yeast cells was detected.